Unraveling the rationale and conducting a comprehensive assessment of KD025 (Belumosudil) as a candidate drug for inhibiting adipogenic differentiation—a systematic review - Barbalho, Sandra Maria; de Alvares Goulart, Ricardo; Minniti, Giulia; Bechara, Marcelo Dib; de Castro, Marcela Vialogo Marques; Dias, Jefferson Aparecido; Laurindo, Lucas Fornari (Naunyn-Schmiedeberg's archives of pharmacology, 2024)
Rho-associated kinases (ROCKs) are crucial during the adipocyte differentiation process. KD025 ( Belumosudil ) is a newly developed inhibitor that selectively targets ROCK2. It has exhibited consistent efficacy in impeding adipogenesis across a spectrum of in vitro models of adipogenic differentiation. Given the novelty of this treatment, a comprehensive systematic review has not been conducted yet. This systematic review aims to fill this knowledge void by providing readers with an extensive examination of the rationale behind KD025 and its impacts on adipogenesis. Preclinical evidence was gathered owing to the absence of clinical trials. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were followed, and the study’s quality was assessed using the Joanna Briggs Institute (JBI) Checklist Critical Appraisal Tool for Systematic Reviews. In various in vitro models, such as 3T3-L1 cells, human orbital fibroblasts, and human adipose-derived stem cells, KD025 demonstrated potent anti-adipogenic actions. At a molecular level, KD025 had significant effects, including decreasing fibronectin (Fn) expression, inhibiting ROCK2 and CK2 activity, suppressing lipid droplet formation, and reducing the expression of proadipogenic genes peroxisome proliferator-activated receptor gamma (PPARγ) and CCAAT/enhancer-binding protein α (C/EBPα). Additionally, KD025 resulted in the suppression of fatty acid-binding protein 4 (FABP4 or AP2) expression, a decrease in sterol regulatory element binding protein 1c (SREBP-1c) and Glut-4 expression. Emphasis must be placed on the fact that while KD025 shows potential in preclinical studies and experimental models, extensive research is crucial to assess its efficacy, safety, and potential therapeutic applications thoroughly and directly in human subjects.